Returns to scale: New evidence from administrative firm-level data - Peter McAdam; Philipp Meinen; Chris Papageorgiou; Patrick Schulte (Deutsche Bundesbank, 2024)
Using a new administrative dataset, we provide fresh micro-level evidence on firms' returns to scale (RTS). We employ a new administrative database, iBACH, which contains extensive high-quality annual balance sheet, financial, and demographic information on more than two million non-financial manufacturing, trade and service corporations for five European countries over 2008-2018. Whereas on average, we find sectoral RTS to be close to one (0.98, with a 0.74 - 1.18 range), 32 percent of firms exhibit decreasing returns, and 10 percent increasing returns to scale (IRTS). Although the RTS values have remained relatively stable, there is evidence of some tendency for them to increase over time. When we allow for imperfect competition, the RTS range tightens to 0.98 - 1.08, with a higher share of IRTS industries (15 percent) and essentially zero DRTS cases. Increasing returns are mostly a feature of manufacturing. Finally, we analyze the relationship between different industry characteristics and our RTS estimates.
Keywords: E2; D2; L1; 330; Firm & sectoral production function estimation; imperfect competition; firm characteristics; Gandhi-Navarro-Rivers; iBACH database